Residual error based adaptive method with an optimal variable scaling parameter for RBF interpolation - Veni, Krishna G.; Satyanarayana, Chirala; Krishareddy, Chenna M. (Zielona Góra: Uniwersytet Zielonogórski)
In infinitely smooth Radial Basis Function (RBF) based interpolation, the scaling parameter plays an important role to obtain an accurate and stable numerical solution. When this method is applied to interpolate a function with sharp gradients, then adaptive methods will also play a significant role in determining an optimal number of centers according to the user desired accuracy.
Keywords: radial basis functions; adaptive residual subsampling; optimal shape parameter